THE EFFECT OF USING THE FLIPPED CLASSROOM MODEL ON THE ABILITY TO WRITE FACTUAL TEXTS STUDENTS OF THE INDONESIAN LANGUAGE STUDY PROGRAM - Hayu Afdetis Mana, Lira; Komala Sari, Lusi; Harti, Laspida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the effect of the Flipped Classroom learning method on the ability to write factual texts, including reconstruction texts, explanation texts, and procedural texts. The Flipped Classroom method shifts the traditional learning paradigm by moving theoretical learning activities outside the classroom and focusing classroom activities on discussions and practice. This study uses a quantitative approach with an experimental design. The research sample consists of 67 students randomly selected from three different classes. The experimental group used the Flipped Classroom method, while the control group used the traditional learning method. The results showed a significant improvement in the ability to write factual texts in the experimental group compared to the control group. This improvement is attributed to more intensive interaction between students and teachers, as well as opportunities for students to better understand the material through self-directed learning. This study concludes that the Flipped Classroom method is effective in improving students' ability to write factual texts and recommends the application of this method as an alternative in writing instruction.